Design, synthesis and evaluation of bitopic arylpiperazinephenyl-1, 2, 4-oxadiazoles as preferential dopamine D3 receptor ligands. Issue 2 (15th January 2016) - Cao, Yongkai; Min, Chengchun; Acharya, Srijan; Kim, Kyeong-Man; Cheon, Seung Hoon
Graphical abstract: Abstract: The dopamine D3 receptor (D3R) was proposed as a therapeutic target for drug development to treat drug abuse and addiction and neuropsychiatric disorders. Several D3R-selective modulators over the dopamine D2 receptor (D2R) can avoid extrapyramidal symptoms (EPS) and hyperprolactinemia. However, few biased D3R ligands were identified or showed a narrow range of selectivity at the D3R over D2R because of their high sequence homology. Herein, we designed, synthesized and evaluated the binding affinity of a series of bitopic ligands: arypiperazine-phenyl-1, 2, 4-oxadiazoles. Compound9e ·HCl was the most potent and selective D3R modulator among these bitopic ligands. Molecular modeling revealed that D3R selectivity depends on the divergence of secondary binding pocket (SBP) in D3R and D2R. Specifically, non-conserved Tyr36, EL1 especially non-conserved Thr92 and Gly94, and EL2 Val180, Cys181 and Ser182 of D3R may contribute to D3R specificity over D2R.